2004
DOI: 10.1515/bc.2004.143
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression analysis of a variety of apoptosis-related genes, including the novel gene of the BCL2-family, BCL2L12, in HL-60 leukemia cells after treatment with carboplatin and doxorubicin

Abstract: Apoptosis is a type of programmed cell death involved in many crucial biological processes. It represents the basic mechanism for the action of chemotherapeutic agents, such as doxorubicin and carboplatin. Both are able to cause cell death through the induction of apoptosis in the human leukemic cell line HL-60. We investigated the possible alterations in the expression of apoptosis-related genes, including the novel BCL2L12 gene, which was recently cloned in our group. The kinetics of apoptosis induction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
0
26
0
6
Order By: Relevance
“…BCL2 mRNA levels also varied in breast cancer cell lines, mainly in the MCF-7, after treatment with anticancer drugs; predominantly benzo-(a)pyrene, 5-FU, tamoxifen, adriamycin, etoposide, camptothecin, Taxol and cisplatin [24] . Modulations were also observed in HL-60 leukemic cells after treatment with topotecan and methotrexate [25] , as well as carboplatin and doxorubicin [26] .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…BCL2 mRNA levels also varied in breast cancer cell lines, mainly in the MCF-7, after treatment with anticancer drugs; predominantly benzo-(a)pyrene, 5-FU, tamoxifen, adriamycin, etoposide, camptothecin, Taxol and cisplatin [24] . Modulations were also observed in HL-60 leukemic cells after treatment with topotecan and methotrexate [25] , as well as carboplatin and doxorubicin [26] .…”
Section: Discussionmentioning
confidence: 92%
“…These mutations are functional and they inhibit the proapoptotic activity of the protein, thus contributing to carcinogenesis [27] . Gene expression of BAX at the mRNA level has been detected to fluctuate in the breast cancer cell line MCF-7 after being exposed to chemotherapeutic agents, such as benzo-(a)pyrene, lindane, adriamycin, etoposide, camptothecin, Taxol and cisplatin [24] , and additionally in the HL-60 cells after treatment with carboplatin [26] and etoposide [28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies in human leukemia cell lines have revealed notable alterations of BCL2L12 mRNA expression in HL-60 acute promyelocytic leukemia cells after treatment with various chemotherapeutic drugs, including cisplatin, carboplatin, doxorubicin, methotrexate, etoposide, topotecan, vincristine, and taxol [27][28][29][30][31], as well as in SHI-1 acute monocytic leukemia cells after treatment with bortezomib [32]. Recently, it has also been proposed that BCL2L12 and BCL2L12-A may play an important role in cisplatin-induced apoptosis in MDA-MB-231 breast adenocarcinoma cells [33,34].…”
Section: Introductionmentioning
confidence: 99%